Neutrophil-Dependent Immunity During Pulmonary Infections and Inflammations - Effah, Clement Yaw; Drokow, Emmanuel Kwateng; Agboyibor, Clement; Ding, Lihua; He, Sitian; Liu, Shaohua; Akorli, Senyo Yao; Nuamah, Emmanuel; Sun, Tongwen; Zhou, Xiaolei; Liu, Hong; Xu, Zhiwei; et al. (Frontiers in Immunology, 2021)
Rapid recruitment of neutrophils to an inflamed site is one of the hallmarks of an effective host defense mechanism. The main pathway through which this happens is by the innate immune response. Neutrophils, which play an important part in innate immune defence, migrate into lungs through the modulation actions of chemokines to execute a variety of pro-inflammatory functions. Despite the importance of chemokines in host immunity, little has been discussed on their roles in host immunity. A holistic understanding of neutrophil recruitment, pattern recognition pathways, the roles of chemokines and the pathophysiological roles of neutrophils in host immunity may allow for new approaches in the treatment of infectious and inflammatory disease of the lung. Herein, this review aims at highlighting some of the developments in lung neutrophil-immunity by focusing on the functions and roles of CXC/CC chemokines and pattern recognition receptors in neutrophil immunity during pulmonary inflammations. The pathophysiological roles of neutrophils in COVID-19 and thromboembolism have also been summarized. We finally summarized various neutrophil biomarkers that can be utilized as prognostic molecules in pulmonary inflammations and discussed various neutrophil-targeted therapies for neutrophil-driven pulmonary inflammatory diseases.